Efektivitas Penerapan Aplikasi Inlislite dalam Menunjang Kegiatan Katalogisasi di Dinas Perpustakaan dan Kearsipan Provinsi Jawa Timur - Wulandari, Azizah Putri Rizky; Hertati, Diana (VISA: Journal of Vision and Ideas, 2025)
The use of the Inlislite application at the East Java Provincial Library and Archives Service since 2010 has improved efficiency in cataloguing. With 11 staff managing the system, errors are rare. However, the main challenge is data security and the need for competent IT personnel. On average, cataloguers can input 5-10 book titles per day, although OPAC updates are still done manually. The availability of tools for data backup shows concern for the protection of important information. In addition, training for new staff helps improve understanding and quality of data management. Overall, Inlislite provides great benefits, but there are still challenges that need to be overcome to optimise the use of the system.